Prospects and Limitations of Agriculture Industrialization in Nepal - Paudel, Mina Nath (Agronomy Journal of Nepal, 2016)
Nepal is culturally an agriculture based country. One third of GDP comes from agriculture and there are numerous opportunities in agriculture mainly because of varied agro-climate prevailed in the country. Niche specific commodities that have comparative advantage could be produced in fair quantity to meet the demand of huge market of neighboring India and China as purchasing capacity of people in those countries has improved markedly mainly for quality agriculture commodities. Trade deficit, food insecurity, income generation, poverty reduction, and employment generation could be addressed by turning present status of subsistence agriculture into robust, vibrant and commercial agriculture through technology led agro-industrialization. There are agro-commodities which are imported from India and other countries in huge quantity by the scarce hard currency earned through remittance. Evidence shows that almost 70% of the remittance is spent for agriculture commodities which have high potentiality to produce within the country even after local consumption. Such produce could be exported to other countries to mitigate trade imbalance, enhance export promotion and import reduction and promote graduating Nepal from LDC to DC within the stipulated time frame as proposed a couple of years ago by the government of Nepal. Nepal should come up with functional, pragmatic and implementable agriculture plan and policy to harness huge possibility of agriculture commercialization to meet the consumption demand per se within and outside the country. This paper highlights to address prospects and limitations of agriculture commercialization and suggests some way forward to make agriculture more vibrant and robust to address trade deficit, food and nutritional insecurity and livelihood enhancement of Nepalese as a whole thereby Nepal can tailor her pace of development with neighboring countries to meet the aspiration of Nepalese in the 21st century. Agronomy Journal of Nepal (Agron JN) vol. 4, 2016, Page: 38-63